2010
DOI: 10.1016/j.bcp.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the flavonoids apigenin, kaempferol, and quercetin on the function of organic anion transporting polypeptides 1A2 and 2B1

Abstract: Influence of the flavonoids apigenin; kaempferol and quercetin on the function of organic anion transporting polypeptides 1A2 and 2B1, Biochemical Pharmacology (2010), doi:10.1016/j.bcp.2010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 34 publications
(56 reference statements)
5
68
0
Order By: Relevance
“…Of this, about 13.8 mg/d is in the form of quercetin-type flavonols (Cao et al, 2010). Several studies showed that quercetin had an inhibitory effect on OATP2B1's function (Mandery et al, 2010;Satoh et al, 2005;Shirasaka et al, 2013a). Our results were consistent with these reports (Figures 2 and 3, and Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Of this, about 13.8 mg/d is in the form of quercetin-type flavonols (Cao et al, 2010). Several studies showed that quercetin had an inhibitory effect on OATP2B1's function (Mandery et al, 2010;Satoh et al, 2005;Shirasaka et al, 2013a). Our results were consistent with these reports (Figures 2 and 3, and Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Inhibition or stimulation of OATP2B1's function by drugs or foods could alter the pharmacokinetics of OATP2B1 substrates and potentially lead to adverse effects. Quite a few interactions between OATP2B1 and natural products have been reported in the literature (Fuchikami et al, 2006;Imanaga et al, 2011;Kock et al, 2013;Li et al, 2014;Mandery et al, 2010;Satoh et al, 2005;Shirasaka et al, 2013a,b;Tapaninen et al, 2010Tapaninen et al, , 2011Roth et al, 2011), suggesting that OATP2B1 could interact with a wide range of natural products. To identify more OATP2B1 modulators from natural products and to avoid potential adverse drug-drug and drug-food interactions, in this work the effects of 27 natural compounds and extracts on the function of OATP2B1 have been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosuvastatin has a high affinity for OATP transporters, as its K m was determined to be 2.6, 4.0, 9.8, and 2.4 mM for OATP1A2, OATP1B1, OATP1B3, and OATP2B1, respectively (Ho et al, 2006). Finally, OATP1A2 is inhibited by various flavonoids, such as naringin, apigenin, kaempferol, quercetin, and several flavonoids found in green tea Mandery et al, 2010;Roth et al, 2011;Misaka et al, 2014). Flavonoids are found in vegetables, fruits, and plants; thus, pharmacokinetic studies using flavonoids focused on intestinal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…HEK-OATP1A2, HEK-OATP1B1, HEK-OATP1B3, and HEK-OATP2B1 cells and the respective vector-transfected control cells (HEK-VC cells) were established as described previously (Leonhardt et al, 2010;Mandery et al, 2010). For competition assays, the cells were seeded in 24-well plates (BD Biosciences, Heidelberg, Germany) in full growth medium (minimal essential medium supplemented with 10% fetal bovine serum, 2 mM L-glutamine, and 2 mM nonessential amino acids; PAA, Coelbe, Germany) for 3 days, at an initial density of 200,000 cells per well.…”
Section: Methodsmentioning
confidence: 99%